2006
DOI: 10.1021/jp0631883
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Opening of Carbon Nanotubes Using Steam

Abstract: Purification and opening of carbon nanotubes has been carried out by treatment of as-made single-wall carbon nanotubes (SWNTs) with pure steam at 1 atm pressure. Treated samples have been characterized by high-resolution transmission electron microscopy and IR and Raman spectroscopy. Comparison between the steam purification and the standard nitric acid purification treatment shows that steam is less aggressive toward damage to the tubular nanotube wall structure and forms fewer functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 22 publications
2
101
0
Order By: Relevance
“…Tobias et al [47] reported that steam can be used effectively for purification of CNTs since steam is a mild oxidizing agent which can remove the amorphous carbon present in samples with less defects on the produced CNTs. Therefore, the results suggest that using Ni-Mn-Al catalyst with steam injection rate of 4.74 g h -1 is optimal for both hydrogen and CNT production in this work.…”
Section: Products Yields and Gas Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobias et al [47] reported that steam can be used effectively for purification of CNTs since steam is a mild oxidizing agent which can remove the amorphous carbon present in samples with less defects on the produced CNTs. Therefore, the results suggest that using Ni-Mn-Al catalyst with steam injection rate of 4.74 g h -1 is optimal for both hydrogen and CNT production in this work.…”
Section: Products Yields and Gas Compositionsmentioning
confidence: 99%
“…Therefore, the quality of the carbon nanotubes in terms of purity was improved when the steam was added with the injection rate of 2.85 or 4.74 g h -1 . It is suggested that amorphous carbons were removed in the presence of a certain amount of steam [47]. The carbon deposits on the surface of Ni-Mn-Al catalyst with weaker metal support interaction, prepared by the calcination at lower temperature (300°C), were also characterized using laser Raman spectroscopy.…”
Section: Raman Analysis For Reacted Ni-mn-al Catalystmentioning
confidence: 99%
“…However, this might not be the only reason why uranium shows lower oxidation state with longer solvothermal treatment. As we discussed previously, UO2 crystallized better when prolonging the solvothermal time, which generally should show greater resistance to oxidation when exposed to air [38,39]. This effect should also be taken into account.…”
Section: Catalytic Activities For 4-nitrophenol Reductionmentioning
confidence: 83%
“…Using a density value of 2.2 g cm −3 for carbon and 3.6 g cm −3 , we can calculate a 0.7 Wh cm −3 drop of energy density (from 2.1 to 1.4 Wh cm −3 ) at a carbon content of 23 wt%. In general, we can see that the high amount of carbon, although of the more conductive graphitic type, has a negative effect on the electrochemical and battery performance of LiFePO 4 but different approaches are under consideration to lower the amount of carbon such as: sintering the material in different gas composition in hydrogen and steam that are commonly used to purify carbon nanotubes [30]; or using different sizes of PS spheres [18]. Fig.…”
Section: Resultsmentioning
confidence: 99%